T817MA attenuates oxidative stress and ER stress via the HSP70–HSP90 pathway after brain ischemia in vitro and in vivo - Wang, Tao; Pan, Ya-Juan; Zhang, Mei-Mei; Wang, Xuan; Li, Wei; Lv, Jian-Meng (Frontiers in Pharmacology, 2025)
Ischemic stroke imposes a substantial global burden, with oxidative stress and endoplasmic reticulum (ER) stress being the pivotal pathological mechanisms. Heat shock proteins (HSPs), especially HSP70 and HSP90, play critical roles in neuroprotection against ischemic injury. In this study, we investigate the neuroprotective effects of T817MA, a novel compound, and its underlying mechanisms in vitro and in vivo. Using oxygen–glucose deprivation (OGD)-treated HT22 cells and a middle cerebral artery occlusion (MCAO) mouse model, we found that T817MA (1 μM–3 μM) significantly attenuated OGD-induced neuronal injury, as evidenced by improved cell viability, reduced lactate dehydrogenase (LDH) release, and decreased reactive oxygen species (ROS) production. Mechanistically, T817MA suppressed ER stress by inhibiting CHOP expression and reducing intracellular Ca2+ release from the ER. Western blot analysis revealed that T817MA upregulated HSP70 while downregulating HSP90 in OGD-treated cells and MCAO mice. Blocking HSP70 with PES abolished T817MA-mediated protection, confirming the essential role of the HSP70–HSP90 pathway. In vivo, oral administration of T817MA (30 mg/kg) for 20 days prior to MCAO reduced brain edema, preserved NeuN+ neurons, and produced transient improvements in neurological function during the early post-ischemic period (3–5 days), although no lasting behavioral recovery was observed. Immunostaining and Western blotting showed that T817MA mitigated ER stress (i.e., reduced CHOP) and modulated HSP70/HSP90 expression in the ischemic brain. Collectively, T817MA exerts neuroprotection against brain ischemia by alleviating oxidative and ER stress via the HSP70–HSP90 signaling pathway, thus highlighting its potential as a therapeutic agent for ischemic stroke.